2018
DOI: 10.2174/1874210601812010340
|View full text |Cite
|
Sign up to set email alerts
|

Oral Ketorolac with Inferior Alveolar Nerve Block for Irreversible Pulpitis: A Systematic Review and Meta-analysis

Abstract: Background:Ketorolac has advantages over other analgesics as a pre-anaesthetic medication. Considering this in mind, the present meta-analysis aims to identify the effect of oral ketorolac premedication on the anaesthetic efficacy of Inferior Alveolar Nerve Block (IANB) in patients with irreversible pulpitis.Methods:Full-texts of eligible studies were obtained from electronic databases. The extracted data was analysed using non-Cochrane mode in RevMan 5.0 software. Relative risk [95% CI] was calculated for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…3 Sivaramakrishnan et al concluded in their study that oral ketorolac can be successfully administered as a premedication before conventional inferior alveolar nerve block for endodontic treatment for irreversible pulpitis. 19 Our study also correlated with Vieyra et al who concluded that oral ketorolac was as safe and effective for postoperative pain relief in patients with symptomatic apical periodontitis. 20 Our study is contradictory to the study by de Geus et al who concluded that ibuprofen premedication is beneficial for the success of inferior alveolar nerve block in patients with irreversible pulpitis.…”
Section: Brief History Of Nsaidssupporting
confidence: 87%
“…3 Sivaramakrishnan et al concluded in their study that oral ketorolac can be successfully administered as a premedication before conventional inferior alveolar nerve block for endodontic treatment for irreversible pulpitis. 19 Our study also correlated with Vieyra et al who concluded that oral ketorolac was as safe and effective for postoperative pain relief in patients with symptomatic apical periodontitis. 20 Our study is contradictory to the study by de Geus et al who concluded that ibuprofen premedication is beneficial for the success of inferior alveolar nerve block in patients with irreversible pulpitis.…”
Section: Brief History Of Nsaidssupporting
confidence: 87%
“…Also combined compositions of thin films were selected, which based on the same polymers with addition of Carbopol ® 971P NF in concentration of 0.05 % (▶Table 1). There were added 0.02 g ketorolac trometamine to produce the thin film covering 78.5 cm 2 at 25 ml of purified water, concentration of ketorolac is equivalent to the recommended effective single-dose [6,7].…”
Section: Resultsmentioning
confidence: 99%
“…has shown the effectiveness in the treatment of inflammation in oral cavity and sharp pain, when it was administered orally, buccally, parenterally and intranasally [7][8][9]. However, using the ketorolac trometamine in such dosage form as a dental film will allow providing targeted treatment of the affected areas, as well as to modify release and correct the intensity of the side effects.…”
Section: Development Of Composition and Technologies Of Dental Film Wmentioning
confidence: 99%
“…Several systematic reviews and meta‐analyses have been carried out to introduce the techniques for enhancing the efficacy of IANBs, particularly for irreversible pulpitis (Larocca de Geus et al, 2020; Nagendrababu et al, 2021; Pulikkotil et al, 2018; Tupyota et al, 2018; Zanjir et al, 2019). Previous meta‐analyses reported that increasing the volume of the anaesthetic solution (Nagendrababu et al, 2021; Tupyota et al, 2018), choosing articaine (Larocca de Geus et al, 2020) or mepivacaine (Nagendrababu et al, 2019) as an anaesthetic solution, and using oral premedication (Tupyota et al, 2018) such as ibuprofen (Nagendrababuet al, 2018), ketorolac (Sivaramakrishnan & Sridharan, 2018), and tramadol (Pulikkotil et al, 2018), increase the success rate of IANB. Supplemental injection, particularly intraosseous, and buccal and lingual infiltrations with articaine, also increases the efficacy of IANB (Zanjir et al, 2019).…”
Section: Discussionmentioning
confidence: 99%